Myelolipomas and other fatty tumours of the adrenals - Khater, Nazih (Elsevier, 2011)
BACKGROUND: Lipomatous tumours of the adrenals are almost always benign. The importance of recognising their characteristic radiological features, leading to their correct treatment, is fundamental, as there has been an increase in the identification of these lesions. Our goal was to review all lipomatous tumours of the adrenal glands, particularly myelolipomas, their imaging methods and surgical management, updated in 2011. METHODS: This was a retrospective review of articles published in the USA and Europe, from 1979 to date. The sites from which information was retrieved covered PubMed, Medscape, Clinical Imaging, Histopathology, Urologia Internationalis, Archives of Surgery, JACS, the American Urological Association, BMJ, Medline, and Springer Link. We report areas of controversies in addition to well established guidelines. RESULTS: We reviewed 45 articles, that confirmed, with a high level of evidence-based medicine, that the diagnosis of a lipomatous adrenal tumour is made by various imaging procedures, particularly computed tomography (CT). We emphasise the importance to their management of the initial size of the adrenal mass, its increase in size over time, in addition to the presence of symptoms. CONCLUSION: Lipomatous tumours of the adrenals are most frequently benign. The diagnosis is usually made by various techniques, in particular CT. The fundamental characteristics indicating the necessity of surgical intervention are the symptoms presented, volume of the tumoral mass (>5 cm), and the increase in size of the tumour as shown in two consecutive imaging studies.